Achieving enhanced denitrification via hydrocyclone treatment on mixed liquor recirculation in the anoxic/aerobic process. (December 2017) - Liu, Yi; Wang, Hualin; Xu, Yinxiang; Tu, Qingsong; Chen, Xiurong
Abstract: This work presents the novel application of hydrocyclones for mixed liquor recirculation (MLR) treatment in the anoxic/aerobic (A/O) process to enhance the denitrification process. An exhaustive investigation on treated activated sludge and A/O effluents was conducted in batch and continuous operation tests. The median diameter of the sludge flocs was decreased from 78.82 μm to 15.77–23.31 μm, and the extracellular polymeric substances (EPS) desorption was observed, thus leading to the release of the soluble chemical oxygen demand (SCOD). A marked increase in the BOD5 /TN ratio was consequently achieved, which supplied the carbon source and improved the biodegradability of the MLR. The hydrocyclone treatment also enabled a 7.17% ± 0.93% specific oxygen utilization rate (SOUR) increase at the optimal hydrocyclone intensity of 0.13 MPa, owing to the desorption of positioned microbial secretion from the microorganism cells. The nitrate reductase and nitrite reductase were also improved by 15.13% ± 1.16% and 17.61% ± 1.55%, respectively. The nitrate removal efficiency was enhanced by 13.6%, and the nitrogen oxide gases varied slightly; this behavior was consistent with the variations in the key enzymes involved in denitrification. The A/O process operated in the mode of hydrocyclone-treated MLR, compared with in the conventional mode, resulted in a 15.56% higher TN removal, and the other effluent parameters remained stable. Hydrocyclone disruption is thus a convenient and energy-efficient process with broad implications in denitrification development. Graphical abstract: Highlights: A hydrocyclone was firstly applied for MLR treatment in the A/O process. Activated sludge was disrupted by the hydrocyclone followed by outer EPS desorption. Increased microbial activity and carbon source release were simultaneously achieved. Nitrate removal was increased by 13.6% as well as 15.56% increase of TN removal.